Dynamics of ice cover over a far northern lake : Direct observations of Ward Hunt Lake, Canadian High Arctic, by automated camera. ... : Dynamique du couvert de glace d’un lac dans l'extrême nord : Observations directes du lac Ward Hunt, haut arctique canadien, par caméra automatisée. ... - NEIGE (Nordicana D, 2023)
Long-term monitoring of lakes and fjords on the northern coast of Ellesmere Island, Nunavut, provides information on the effects of climate change on these ecosystems and their seasonal and interannual dynamics. Lake ice cover is a sentinel variable with controlling effects on lake ecosystems, and it is especially sensitive to climate change. This dataset of ice imagery for Ward Hunt Lake (Ward Hunt Island) covers the period 2016-2022 and is a contribution to the NEIGE program (Northern Ellesmere Island in the Global Environment). Weather-resistant time-lapse cameras were installed on metal supports (rods) overlooking the lake in order to observe and document changes in the lake (ice and snow cover, water level) and its watershed (snow, vegetation, ground conditions, wildlife). The dataset has been separated into seasonal or monthly folders to facilitate downloading; note that there was a change of camera model and repositioning in 2017. ... : Le suivi à long terme des lacs et des fjords sur la côte nord de l'île d'Ellesmere, au Nunavut, fournit des informations sur les effets du changement climatique sur ces écosystèmes et leur dynamique saisonnière et interannuelle. La couverture de glace de lac est une variable sentinelle ayant des effets contrôlants sur les écosystèmes lacustres, et elle est particulièrement sensible aux changements climatiques. Cet ensemble de données d'imagerie des glaces pour le lac Ward Hunt (île Ward Hunt) couvre la période 2016-2022 et constitue une contribution au programme NEIGE (Northern Ellesmere Island in the Global Environment). Des caméras time-lapse résistantes aux intempéries ont été installées sur des supports métalliques (tiges) surplombant le lac afin d'observer et de documenter les changements dans le lac (couverture de glace et de neige, niveau d'eau) et son bassin versant (neige, végétation, conditions du sol, faune). L'ensemble de données a été séparé en dossiers saisonniers ou mensuels pour faciliter le ...